Mucosal Antibodies to the C Terminus of Toxin A Prevent Colonization of Clostridium difficile - Hong, Huynh A. (Infect Immun, 2017)
Mucosal immunity is considered important for protection against Clostridium difficile infection (CDI). We show that in hamsters immunized with Bacillus subtilis spores expressing a carboxy-terminal segment (TcdA(26–39)) of C. difficile toxin A, no colonization occurs in protected animals when challenged with C. difficile strain 630. In contrast, animals immunized with toxoids showed no protection and remained fully colonized. Along with neutralizing toxins, antibodies to TcdA(26–39) (but not to toxoids), whether raised to the recombinant protein or to TcdA(26–39) expressed on the B. subtilis spore surface, cross-react with a number of seemingly unrelated proteins expressed on the vegetative cell surface or spore coat of C. difficile. These include two dehydrogenases, AdhE1 and LdhA, as well as the CdeC protein that is present on the spore. Anti-TcdA(26–39) mucosal antibodies obtained following immunization with recombinant B. subtilis spores were able to reduce the adhesion of C. difficile to mucus-producing intestinal cells. This cross-reaction is intriguing yet important since it illustrates the importance of mucosal immunity for complete protection against CDI.